Social and parental support as moderators of the effects of homophobic bullying on psychological distress in youth - António, R.; Moleiro, C. (Psychology in the Schools, 2015)
The aim of this study was to explore homophobic bullying in Portugal, including its forms, prevalence, and consequences, and to verify whether parental and social support moderated the effects of homophobic bullying for victims. An online questionnaire was completed by 211 female and male students, aged 12 to 20 years. Results showed that psychological violence prevailed, male students were more often victims than female students were, and lesbian, gay, and bisexual adolescents were victims more often than their heterosexual peers were. The emotional impact on victims was higher when social support was low, including suicidal ideation and school difficulties. Furthermore, a main effect of parental support was found for emotional and behavioral distress indices experienced by adolescents.